Allomyrina dichotoma larvae extract as a novel tenderizer on brined pork loin and changes in quality based on extraction methods - Tae-Kyung Kim; Hyun-Jung Yun; Yea-Ji Kim; Ji Yoon Cha; Yun-Sang Choi (Applied Food Research)
This study investigated the effects of Allomyrina dichotoma larvae extract, a novel food resource, on the tenderization and quality enhancement of brined pork loin. The extraction buffers used were distilled water and 0.58 M saline buffer, and the extracted insect solution and residue were added to the brine. Treatments with insect extracts showed improved tenderization, as evidenced by lower shear force values, enhanced water-holding capacity, and reduced lipid oxidation, suggesting the potential for longer shelf life and improved nutritional quality. These findings provide valuable insights into the use of edible insect extracts in meat processing, highlighting the benefits of this innovative approach for enhancing meat quality for various consumer segments, including older adults. Overall, this study underscores the potential of edible insects as sustainable and effective ingredients in meat-curing processes, offering a promising avenue for the development of more nutritious and palatable meat products.